A sacrificial process for fabrication of biodegradable polymer membranes with submicron thickness. Issue 6 (16th June 2015) - Beardslee, Luke A.; Stolwijk, Judith; Khaladj, Dimitrius A.; Trebak, Mohamed; Halman, Justin; Torrejon, Karen Y.; Niamsiri, Nuttawee; Bergkvist, Magnus
Abstract: A new sacrificial molding process using a single mask has been developed to fabricate ultrathin 2‐dimensional membranes from several biocompatible polymeric materials. The fabrication process is similar to a sacrificial microelectromechanical systems (MEMS) process flow, where a mold is created from a material that can be coated with a biodegradable polymer and subsequently etched away, leaving behind a very thin polymer membrane. In this work, two different sacrificial mold materials, silicon dioxide (SiO2 ) and Liftoff Resist (LOR) were used. Three different biodegradable materials; polycaprolactone (PCL), poly(lactic‐ co ‐glycolic acid) (PLGA), and polyglycidyl methacrylate (PGMA), were chosen as model polymers. We demonstrate that this process is capable of fabricating 200‐500 nm thin, through‐hole polymer membranes with various geometries, pore‐sizes and spatial features approaching 2.5 µm using a mold fabricated via a single contact photolithography exposure. In addition, the membranes can be mounted to support rings made from either SU8 or PCL for easy handling after release. Cell culture compatibility of the fabricated membranes was evaluated with human dermal microvascular endothelial cells (HDMECs) seeded onto the ultrathin porous membranes, where the cells grew and formed confluent layers with well‐established cell‐cell contacts. Furthermore, human trabecular meshwork cells (HTMCs) cultured on these scaffolds showed similar proliferation as on flat PCL substrates, further validating its compatibility. All together, these results demonstrated the feasibility of our sacrificial fabrication process to produce biocompatible, ultra‐thin membranes with defined microstructures (i.e., pores) with the potential to be used as substrates for tissue engineering applications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1192–1201, 2016.